Blurring boundaries: early Sinhala cinema as another Adam’s Bridge between Ceylon and India (1948-1968) - Vilasnee TAMPOE-HAUTIN (E-REA)
Within the context of ambiguous Indo-Sri Lankan relations, I seek to probe the question of cinema as a cultural and political articulation between these two spatialities, transcending colonial boundaries and traditional rivalries. I will argue that nascent cinema coalesced the Indo-Sri Lankan spaces into one whole, structuring networks, constellations and inter-connectivity. How did early cinema become a treading and trading ground and a “global village” (MacLuhan) for citizens of the world, overriding criteria of caste, class, language and religion? But while cinema blurred conventional frontiers and enhanced social and cultural flows across borders during the colonial era, the opposite is true of the post-independent period of the 1950s when movements for the political hegemony of the Sinhala people would rapidly spill over the cinema industry. This paper will thus consider the way the film industry also articulated Sri Lankan ethnicities: at the core of the discussion will be the call by Sinhala “cultural patriots” for a film culture more articulate of Sinhala culture, based on the premise that Dream Merchants from India, the United States and Great Britain were exercising economic and cultural imperialism through the film mode. Conclusively, I will argue that the sense of endangerment to Sinhala culture – whether real or imagined – that gripped a part of the Ceylonese nation, as well as the ensuing 1960s State protectionist policies in favour of ethnic Sinhalese, refer back to how the film industry brings into sharp focus the socio-ethnic and economic malaises that have incessantly borne upon Sri Lanka’s cultural history.